Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Solve for [tex]\( x \)[/tex]:
[tex]\[ x - 9 = 37 \][/tex]


Sagot :

Let's solve the equation step by step:

Given equation:
[tex]\[ x - 9 = 37 \][/tex]

Step 1: Isolate the variable [tex]\( x \)[/tex].

To do this, we need to get rid of the constant term on the left side of the equation. We can do this by adding 9 to both sides of the equation:
[tex]\[ x - 9 + 9 = 37 + 9 \][/tex]

Step 2: Simplify both sides of the equation.

On the left side:
[tex]\[ x - 9 + 9 = x \][/tex]
since [tex]\(-9 + 9 = 0\)[/tex].

On the right side:
[tex]\[ 37 + 9 = 46 \][/tex]

So, the simplified equation is:
[tex]\[ x = 46 \][/tex]

Thus, the solution to the equation [tex]\( x - 9 = 37 \)[/tex] is:
[tex]\[ x = 46 \][/tex]

Answer:

hello

Step-by-step explanation:

x-9=37

x-9+9=37+9

x=46